EIF venture capital, private equity mid-market & business angels surveys 2020: Market sentiment - COVID-19 impact - Policy measures - Helmut Krämer-Eis; Antonia Botsari; Kilian Kiefer; Frank Lang (European Investment Fund (EIF), 2021)
2020 was an unprecedented and remarkable year, and also a year with high uncertainty and increased information needs. The EIF VC Survey, the EIF Private Equity Mid-Market Survey, and the EIF Business Angels Survey (the largest regular survey exercises among GPs and Business Angels on a pan-European level) provide an opportunity to retrieve unique market insights. On an exceptional basis, two waves for each of the three surveys were performed in 2020. This publication summarises and compares the main results, providing a detailed picture of the recent developments. The paper focuses on the market sentiment and the impact of COVID-19 on investors, their portfolio, fundraising and investments (including ESG considerations), and finally, it shows respondents' opinion with regard to crisis-related policy measures.
Keywords: 330